2011
DOI: 10.2807/ese.16.22.19879-en
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B prevention in Victoria, Australia – the potential to protect

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…A more concerted action on the part of medical educators and policymakers is needed to address the many missed opportunities to screen for CHB, vaccinate those susceptible, and prevent disease complications 25. Since hepatitis B treatment has changed radically in the last two decades (ie, during the time period most of today’s practicing GPs were already in medical practice), more opportunities to learn about the modern management of CHB infection are acutely needed.…”
Section: Discussionmentioning
confidence: 99%
“…A more concerted action on the part of medical educators and policymakers is needed to address the many missed opportunities to screen for CHB, vaccinate those susceptible, and prevent disease complications 25. Since hepatitis B treatment has changed radically in the last two decades (ie, during the time period most of today’s practicing GPs were already in medical practice), more opportunities to learn about the modern management of CHB infection are acutely needed.…”
Section: Discussionmentioning
confidence: 99%
“…5 While compliance with notification requirements is high among laboratories, historically only a minority of health practitioners complied with these regulations in relation to unspecified HBV and HCV. 16 Although laboratory notifications can provide case counts and core demographic information such as age, sex and area of residence, variables such as Aboriginal and Torres Strait Islander status, country of birth, occupation and risk factors for infection can only be provided by the diagnosing doctor. 16 Although laboratory notifications can provide case counts and core demographic information such as age, sex and area of residence, variables such as Aboriginal and Torres Strait Islander status, country of birth, occupation and risk factors for infection can only be provided by the diagnosing doctor.…”
mentioning
confidence: 99%
“…3 We found that, although GPs working in a CHB high-prevalence area were confident with contact management and believed it was primarily their responsibility, the majority encountered difficulties when doing this. If GPs are to successfully have an increased role in preventing ongoing transmission through screening 2 , a system that facilitates contact management and addresses the barriers encountered is required.…”
Section: Discussionmentioning
confidence: 93%
“…1 The Australian National hepatitis B strategy [2014][2015][2016][2017] 2 acknowledges the increasing public health burden of CHB and emphasises the management of CHB in the primary care setting, and the testing and vaccination of priority populations, including close contacts of known cases. Close contacts are most at risk of infection; however, a previous study demonstrated that recommended screening and vaccination of close contacts is occurring suboptimally 3 , despite the availability of a free hepatitis B vaccine for contacts in Australia. The Sydney and South Western Sydney Local Health Districts (S&SWSLHDs) have the highest prevalence of CHB in New South Wales.…”
Section: Introductionmentioning
confidence: 99%